2016
DOI: 10.1208/s12249-015-0475-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Controlled-Release Fine Particles Using a Dry Coating Method

Abstract: Abstract. Wet coating methods use organic solvents to prepare layered particles that provide controlledrelease medications. However, this approach has disadvantages in that it can cause particle agglomeration, reduce pharmaceutical stability, and leave residual organic solvents. We used a dry coating method to overcome these issues. Fine particles (less than 50 μm in diameter) of controlled-release theophylline were created using theophylline (TP; model drug), polyethylene glycol 20,000 (PEG; drug fixative), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(83 citation statements)
references
References 17 publications
0
83
0
Order By: Relevance
“…Coating technologies and nanoparticles are always used to produce the function preparations with ability of controlled 23,24 and target release 25 and to improve the palatability of the poor-tasting drugs. 26 However, the single-coating granules, tablets, capsules, and other formulations will be chewed up by Thus, the coated drugs will be released and attached with the taste buds of animal mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Coating technologies and nanoparticles are always used to produce the function preparations with ability of controlled 23,24 and target release 25 and to improve the palatability of the poor-tasting drugs. 26 However, the single-coating granules, tablets, capsules, and other formulations will be chewed up by Thus, the coated drugs will be released and attached with the taste buds of animal mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, further improved coating performance was achieved with the use of porous nanoparticle agglomerates as guest particles, due to the formation of fine fragments under mechanical stress (37). In addition, in another study, an ultrahigh-speed mixer was used to achieve coating for cores as small as 16μm, and multi-layer coated single-core particles with less than 50μm in diameter were finally prepared (38). More specifically, the cornstarch core was coated with a drug reservoir layer and a controlled-release layer where PEG 20,000 worked as drug fixative, while hydrogenated castor oil and hydrogenated rapeseed oil played a role in controlling drug release.…”
Section: Dry Coating Techniquementioning
confidence: 99%
“…More specifically, the cornstarch core was coated with a drug reservoir layer and a controlled-release layer where PEG 20,000 worked as drug fixative, while hydrogenated castor oil and hydrogenated rapeseed oil played a role in controlling drug release. Evidence indicated that the multi-layer coated single-core particles produced could be applied in sustained-release systems (38).…”
Section: Dry Coating Techniquementioning
confidence: 99%
“…High surface area of FiUlFiPs is reasoning for receiving interest 1,2,4 . Researchers (scientists and engineers) in pharmaceutical sectors working extensively in finding applications and taking advantage of many worthy properties and new functionalities attributed to FiUlFiPs, as drug delivery system/carriers 1,2,5 .…”
Section: Introductionmentioning
confidence: 99%